Brain-Based Learning (BBL) Strategy on Students’ Vocabulary Mastery - Mima, Fitri Esa Ulva; Reftyawati, Dian (Journal of Linguistics and Social Sciences, 2023)
The researcher used the Brain-Based Learning Strategy to help students understand the vocabulary contained in descriptive reading texts. Brain-based learning strategies are also used to describe applying a theory about the brain to help children maximize their learning potential. A quasi-experimental pre-and post-test design was used in this research. The population of this research is the seventh-grade students of SMPN 1 Sumberjaya West Lampung. The researchers used a cluster random sampling technique for sample selection. The researcher used instruments (Multiple Choice Questions) in the form of research with pre-tests and post-tests to collect data. This research has normal and homogeneous data results, so the hypothesis test used a parametric, independent sample t-test. Based on the analysis of data calculations in hypothesis testing, a significant effect could be seen in the dependent sample t-test table where the value of Sig. (2tailed) of the same variant, which is 0.01 < 0.05, means that Ho is rejected, and Ha is accepted that the Brain-Based Learning Strategy could positively and better influence students’ Vocabulary mastery